1993
DOI: 10.1021/j100108a010
|View full text |Cite
|
Sign up to set email alerts
|

Electron correlation effects in hyperpolarizabilities of p-nitroaniline

Abstract: The importance of including electron correlation effects in the determination of the equilibrium structure and hyperpolarizabilities of p-nitroaniline is investigated. Second-order perturbation theory gives static hyperpolarizabilities which are 88% to 100% larger than those obtained without electron correlation. These values are scaled by a self-consistent field frequency-dependent contribution for comparison with experimental measurements.Despite the large increase in ß(-2 ; , ) from electron correlation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
190
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(217 citation statements)
references
References 9 publications
(10 reference statements)
25
190
1
1
Order By: Relevance
“…[45][46][47][48][49][50][51] We optimized the geometry of the molecule in the C 2v symmetry. This geometry however results in a vibrational mode with an imaginary frequency with modulus 238 cm −1 , meaning it is actually a saddle point.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…[45][46][47][48][49][50][51] We optimized the geometry of the molecule in the C 2v symmetry. This geometry however results in a vibrational mode with an imaginary frequency with modulus 238 cm −1 , meaning it is actually a saddle point.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Because full high-level quantum chemical calculations are prohibitively expensive on an intact triple helix but achievable on the amide chromophore, this stepwise approach represents a reasonable compromise between computational cost and accuracy in the recovered fibril hyperpolarizability. Although previous studies have reported errors in the absolute hyperpolarizabilities in Hartree-Fock (HF) calculations of charge-transfer chromophores from neglect of electron correlation effects, the overall polarization dependence does not appear to be as sensitively dependent on the level of theory (52). Similarly, solvent effects have also been shown to impact the magnitude of the hyperpolarizability in chargetransfer chromophores, but less information is available on the impact of such factors on the polarization-dependence (53).…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…[8][9][10][11] This has generated much interest around this kind of compounds owing to the applications of materials with large hyperpolarizabilities in nonlinear optics [12][13][14][15][16][17][18][19] (NLO), and a considerable amount of effort in this area of research has been devoted to the theoretical prediction of NLO properties via computational methods of quantum chemistry. [19][20][21][22][23][24][25][26][27][28] It was recognized early on that the theoretical determination of hyperpolarizabilities was very challenging for ab initio and semi-empirical methods. 8,12,20 The advent of modern density functional theory (DFT) methods, very successful in many areas across chemistry and materials science, does not solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28] It was recognized early on that the theoretical determination of hyperpolarizabilities was very challenging for ab initio and semi-empirical methods. 8,12,20 The advent of modern density functional theory (DFT) methods, very successful in many areas across chemistry and materials science, does not solve this problem. In fact, the description of CT excitations by time-dependent (TD)DFT using popular global hybrids and generalized gradient approximations (GGAs) is fundamentally flawed, often leading to gross underestimations of E CT and, consequently, exaggeration of β T z .…”
Section: Introductionmentioning
confidence: 99%